2001
DOI: 10.1080/09638280110067180
|View full text |Cite
|
Sign up to set email alerts
|

Serial plaster casting to correct equino-varus deformity of the ankle following acquired brain injury in adults

Abstract: Serial casting should be considered as an adjunct to therapy aimed at improving functional mobility. A variety of therapeutic interventions have been used to augment the effect of the casting regime. Factors that have been demonstrated to be associated with a favourable outcome from serial casting, and recommendations for future research are also discussed in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Muscle and soft tissue shortening with loss of passive joint range of movement is common and associated with pain, further spasticity and loss of function. 13 Spasticity, contracture and weakness of the calf muscles frequently occur together and cause considerable disability; restricting ankle dorsiflexion, disrupting balance and interfering with functional mobility. 2,4 Reduced mechanical and gravitational loads due to muscle atrophy and limited weight-bearing remove an important stimulus for maintaining bone mineral density and increase the risk of fragility fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle and soft tissue shortening with loss of passive joint range of movement is common and associated with pain, further spasticity and loss of function. 13 Spasticity, contracture and weakness of the calf muscles frequently occur together and cause considerable disability; restricting ankle dorsiflexion, disrupting balance and interfering with functional mobility. 2,4 Reduced mechanical and gravitational loads due to muscle atrophy and limited weight-bearing remove an important stimulus for maintaining bone mineral density and increase the risk of fragility fractures.…”
Section: Introductionmentioning
confidence: 99%
“…13 Spasticity, contracture and weakness of the calf muscles frequently occur together and cause considerable disability; restricting ankle dorsiflexion, disrupting balance and interfering with functional mobility. 2,4 Reduced mechanical and gravitational loads due to muscle atrophy and limited weight-bearing remove an important stimulus for maintaining bone mineral density and increase the risk of fragility fractures. 46 Substantial rapid bone loss following spinal cord injury is well documented and bone loss following stroke is increasingly reported along with high rates of fragility fracture in both populations.…”
Section: Introductionmentioning
confidence: 99%
“…Yarkony and Sahgal (1987), in a study of 75 brain injured adults admitted for in-patient rehabilitation, found a staggering 84% of patients presented with a contracture, which amplified proportionately with an increased duration of coma. Reasoning for such a high incidence in this population has been predominantly attributed to spasticity induced posturing (Booth, Doyle, & Montgomery, 1983;Singer, Singer, & Allison, 2001). However, this may also be due to injuries such as fractures or dislocations (Lehmkuhl et al, 1990), or heterotrophic ossification (Whyte & Glenn, 1986) and soft tissue shortening as a direct result of immobility and sustained posturing (Singer et al, 2001).…”
Section: Prevention and Management Of Joint Contracturesmentioning
confidence: 98%
“…Reasoning for such a high incidence in this population has been predominantly attributed to spasticity induced posturing (Booth, Doyle, & Montgomery, 1983;Singer, Singer, & Allison, 2001). However, this may also be due to injuries such as fractures or dislocations (Lehmkuhl et al, 1990), or heterotrophic ossification (Whyte & Glenn, 1986) and soft tissue shortening as a direct result of immobility and sustained posturing (Singer et al, 2001). The most common sites for development of contractures in the brain injured adult are hips, elbows, ankles, and shoulders (Yarkony & Sahgal, 1987).…”
Section: Prevention and Management Of Joint Contracturesmentioning
confidence: 98%
See 1 more Smart Citation